Increased co-expression of 4-1BB with PD-1 on CD8+ tumor-infiltrating lymphocytes is associated with improved prognosis and immunotherapy response in cervical cancer - Zhu, Xiaonan; Feng, Yaning; Fan, Peiwen; Dong, Danning; Yuan, Jianlin; Chang, Cheng; Wang, Ruozheng (Frontiers in Oncology, 2024)
The combination of agonistic antibodies with immune checkpoint inhibitors presents a promising avenue for cancer immunotherapy. Our objective is to explore the co-expression of 4-1BB, ICOS, CD28, with PD-1 on CD8+ T cells in the peripheral blood and tumor tissue of cervical cancer(CC) patients, with a specific focus on the association between the co-expression levels of 4-1BB with PD-1 and clinical features, prognosis as well as immunotherapy response. The goal is to offer valuable insights into cervical cancer immunotherapy.The combination of agonistic antibodies with immune checkpoint inhibitors is a promising cancer immunotherapy option.